Kekosongan Hukum dalam Hal Mengadili Permohonan Keputusan Tata Usaha Negara Fiktif Positif - Alandi, Hansen; Mayasari, Dian Ety (Wajah Hukum, 2024)
Indonesia established a State Administrative Court to resolve disputes between the government and the community. Initially, the State Administrative Court had the authority to make decisions on accepting positive fictitious applications based on the Government Administration Law, but since the introduction of the Job Creation Law, the authority of the State Administrative Court has been abolished. So there will be a judicial review of the Job Creation Law. Decision Number 10/PUU-XX/2022 is a judicial review of the Job Creation Law. The decision explains that the application cannot be accepted because it is still premature because the Job Creation Law has still been formally revised for two years since 2020. This research is normative juridical research. The result of this research is that there is a legal vacuum in the authority to grant acceptance of positive fictitious applications because the Job Creation Law does not regulate it, so that if the Government still does not regulate this matter, then the Government must create a new institution that can provide decisions on accepting positive fictitious applications.